(untitled) (Journal of Pharmaceutical Negative Results, 2019)
Background: In oncology, major surgical interventions are often followed by an interim period of 3–6 months allowing the patient to recover,following which conventional radiotherapy and chemotherapy are initiated. Lack of therapeutic interventions in the interim period allowsproliferation of the residual tumor cells. Thus, introducing a treatment modality in the interim period which inhibits tumor cells withoutexuberating the postsurgical morbidity is the need of the hour. The objective of the study is to fabricate biodegradable cross-linked scaffoldsincorporated with an anticancer drug and optimization of scaffolds for drug release. Materials and Methods: Qualitative and quantitativecharacterization of the drug was done with the help of high‑performance liquid chromatography (HPLC) and ultraviolet (UV) analysis.Three-dimensional (3D) discs of biodegradable scaffolds were prepared with anticancer drugs in aqueous solution in different concentrationsalong with crosslinkers. Discs were studied for their release kinetics with the help of HPLC. Results: HPLC analysis of the 3D‑discs revealednegative results. There was no sign of cisplatin absorbance after the scaffold immersion in the solution. The results were attributed to therapid degradation of the drug. Conclusions: Although scaffold-mediated local chemotherapy holds a great potential to replace conventionalchemotherapy as a postsurgical treatment modality,several practical limitations need to be addressed. Modification in the research methodologyincluding a shorter time for preparing the scaffold and freeze-drying the scaffold material using lyophilization instead of normal drying couldprevent degradation of the drug